Electronic structure study of defects and impurities in oxide semiconductors - Chakrabarty, Aurab (Trinity College (Dublin, Ireland). School of Physics, 2012)
In this work, the crystal and electronic structures of defects and impurities in ZnO and Fe3O4 are studied using first principles calculations. B3LYP hybrid density-functional theory calculations were used with supercell method to evaluate electronic structures and formation energies of intrinsic vacancy defects oxygen(Vo), zinc (Vzn) and zincoxygen pair (Vzno) vacancies. The magnetic exchange couplings of well-separated, singly negatively charged defects were also calculated and were found to be induced by a conduction band electron when the defect levels are partially filled, more than half-filling.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.